A checklist of longhorn beetles (Coleoptera: Cerambycidae) of Serbia - Ilić, Nastas; Ćurčić, Srećko (Zootaxa, 2015)
A checklist of all taxa of the family Cerambycidae (longhorn beetles) from Serbia is presented. The checklist is based on compilation of data gathered both from authors and available literature published up to now. A total of 265 species and 92 subspecies belonging to 109 genera, 48 tribes, and six subfamilies are recorded for Serbia. However, the presence of 28 species listed in Serbia may be questionable. Known distribution and biology of Serbian taxa are provided. The diversity of the fauna of longhorn beetles in Serbia is compared with the surrounding areas in the Balkan Peninsula.